2018
DOI: 10.3390/ijerph16010001
|View full text |Cite
|
Sign up to set email alerts
|

Gcd Gene Diversity of Quinoprotein Glucose Dehydrogenase in the Sediment of Sancha Lake and Its Response to the Environment

Abstract: Quinoprotein glucose dehydrogenase (GDH) is the most important enzyme of inorganic phosphorus-dissolving metabolism, catalyzing the oxidation of glucose to gluconic acid. The insoluble phosphate in the sediment is converted into soluble phosphate, facilitating mass reproduction of algae. Therefore, studying the diversity of gcd genes which encode GDH is beneficial to reveal the microbial group that has a significant influence on the eutrophication of water. Taking the eutrophic Sancha Lake sediments as the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Therefore, from the results of this study, it is speculated that the changes in the overlying water DTP in Sancha Lake were partly due to the dissolution of inorganic and organic phosphorus by Actinobacteria and Cyanobacteria, respectively, releasing DTP into the overlying water. It is suggested that Actinobacteria and Cyanobacteria in sediments have an important role in eutrophication, consistent with the conclusion reported by Li et al [14].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, from the results of this study, it is speculated that the changes in the overlying water DTP in Sancha Lake were partly due to the dissolution of inorganic and organic phosphorus by Actinobacteria and Cyanobacteria, respectively, releasing DTP into the overlying water. It is suggested that Actinobacteria and Cyanobacteria in sediments have an important role in eutrophication, consistent with the conclusion reported by Li et al [14].…”
Section: Resultssupporting
confidence: 91%
“…Sancha Lake is located in Tianfu New District, Sichuan Province, China, 30°13′08″–30°19′56″ N, and 104°11′16″–104°17′16″ E. It is an important source of drinking water and has serious eutrophication issues. The hydrological and morphological characteristics of Sancha Lake and the description of the sampling sites of this study have been described in detail in previous studies [14]. At the nine chosen sampling sites shown in Figure 1, the surface sediments of the lake bed were collected with a Peterson grab and then sealed in polyethylene bags in April 2017 (spring), August 2017 (summer), November 2017 (autumn), and January 2018 (winter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of unpredictable monsoon rain and El-Nino phenomenon both worsens the transboundary haze due to the prolonged and drier weather conditions, especially during the southwest monsoon season [3][4][5][6][7][8]. These conditions increase the severity of air quality due to it containing a noxious mix of air pollutants, such as particulate matter and noxious gases, which are collectively influenced by meteorological factors like ambient temperature, relative humidity, and wind speed [9,10]. Malaysia has been facing this awful phenomenon for almost over a decade, which started in the 1980s up until recent years [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic particles in haze harm human health either in cumulative or acute effects like respiratory mortality, cardiovascular illness, and lung cancer to all groups of people, such as adults and children [9,20]. The small particulate size contained in haze can easily penetrate the lung; at worst, it also goes into the bloodstream [22].…”
Section: Introductionmentioning
confidence: 99%